Admission to Exit: Acquiring Life Skills Whilst in Residential Care in Ghana - Esmeranda Manful; Harriet Takyi; Eunice Gambrah (Social Work & Society, 2015)
In all societies, Ghana not an exception, children are nurtured and equipped with life skills for independent living.  This often takes place within a family unit be it a nuclear, extended or single parent setting.  In Ghana, there is limited empirical evidence on how children in residential care are equipped with life skills to integrate them into society after leaving care.  Drawing on data collected in a qualitative study focusing on a State residential care for children in Ghana, this paper presents the circumstances of the children in care and how they are equipped with life skills.  The findings reveal that majority of the children leave before the age of six.  Although, only few adolescents remain in care yet the carers found it difficult to engage them to acquire life skills.  It is suggested that after-care plans have to be started early for every child, irrespective of how long they are in care, to ensure successful independent living.